Economic Systems Analysis: Statistical Indicators - Sibirskaya, Elena V.; Oveshnikova, Lyudmila V.; Mikheykina, Lilia A.; Lyapina, Innara R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores a wide range of issues related to the methodology, organization, and technologies of analytical work, showing the potential of using analytical tools and statistical indicators for studying socio-economic processes, forecasting, organizing effective companies, and improving managerial decisions. At the level of "living knowledge" in the broad context, it describes the essence of analytical technologies and means of applying analytical and statistical work. The book is of interest to readers regardless of their specialization: scientific research, medicine, pedagogics, law, administrative work, or economic practice. Starting from the premise that readers are familiar with the theory of statistics, which has formulated the general methods and principles of establishing the quantitative characteristics of mass phenomena and processes, it describes the concepts, definitions, indicators and classifications of socio-economic statistics, taking into consideration the international standards and the present-day practice of statistics in Russia. Although concise, the book provides plenty of study material as well as questions at the end of each chapter It is particularly useful for those interested in self-study or remote education, as well as business leaders who are interested in gaining a scientific understanding of their financial and economic activities.
Introduction To Economic Statistics -- Population Statistics -- Statistics Of Living Standards Of Population -- Statistical Study Of Labor Force -- Statistics Of Labor And Company Personnel -- Macroeconomic Indicators In SNA -- Statistics Of Production -- Statistics Of National Wealth -- Statistics Of Production Costs -- Statistics Of Financial Outcomes Of Company Operation.
Keywords: Computational intelligence; Econometrics; Statistics .; Computational Intelligence; Quantitative Economics; Applied Statistics